Measuring Nurses’ Satisfaction in Primary Health Care Centers at Khartoum, Sudan - Yahya Hussein Ahmed Abdalla (Sudan Journal of Medical Sciences)
Background: The primary healthcare sector has experienced significant growth globally, and the nursing workforce has also expanded in recent decades in response to health system reforms. This study aims to assess job satisfaction among primary healthcare nurses in Khartoum, Sudan. Methods: This descriptive cross-sectional study was conducted in 10 primary healthcare centers on 50 nurses who were selected using simple random sampling. Data were collected using an online questionnaire and it was analyzed using SPSS. Results: The findings of this study indicate that the job satisfaction level among nurses working at primary healthcare centers in Khartoum was high (4.4/5). Most nurses reported high satisfaction with all items including protocols, salary, environment, and relationships. The study also found a significant correlation between nurses’ sex and experience with their level of job satisfaction. Female nurses reported significantly higher job satisfaction (4.4/5) compared to male nurses (3.6/5), (p-value = 0.04). Additionally, nurses with fewer years of experience reported significantly higher job satisfaction compared to those with more years of experience (p-value = 0.03). Conclusion: The study concludes that nurses working at primary healthcare centers in Khartoum have high job satisfaction, particularly regarding the working environment, salary, relationships, and availability of guidelines. Female nurses and those with less experience have significantly higher job satisfaction.